2015
DOI: 10.1002/hon.2233
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin level at diagnosis of diffuse large B‐cell lymphoma: an important simple prognostic factor

Abstract: This study compared the value of several simple laboratory parameters with known prognostic models for predicting survival in patients with diffuse large B-cell lymphoma (DLBCL). The data of 157 adult patients with DLBCL diagnosed at Rabin Medical Center in 2004-2008 and treated with R-CHOP immunochemotherapy were retrospectively reviewed. Main clinical features of the cohort were as follows: mean age 63.0 years, 43% male, 63% stage III/IV disease, 28% ECOG performance status >2, 60% elevated lactate dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
54
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 33 publications
7
54
2
3
Order By: Relevance
“…Serum albumin level has been widely reported to be a prognostic factor of solid malignancies and several hematological malignancies . In the present study, hypoalbuminemia was found in 48.4% MCD patients and was associated with poorer OS.…”
Section: Discussioncontrasting
confidence: 97%
“…Serum albumin level has been widely reported to be a prognostic factor of solid malignancies and several hematological malignancies . In the present study, hypoalbuminemia was found in 48.4% MCD patients and was associated with poorer OS.…”
Section: Discussioncontrasting
confidence: 97%
“…Furthermore, a variety of systemic inflammatory biomarkers has been identified and studied in patients with DLBCL, and might provide useful prognostic information (Table 4). These biomarkers include NLR [30,31], serum LDH [32], serum CRP [33,34], GPS [35,36], serum albumin [37,38], and the peripheral blood absolute lymphocyte and monocyte counts [39]. Troppan et al [30 ]reported that DLBCL patients with an NLR score <4 at diagnosis experienced better OS and disease-free survival than patients with a score of ≥4.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found that the prognostic value of sarcopenia was limited in elderly and male patients [32,33]. There are also contradictory reports regarding the prognostic role of hypoalbuminemia with various cut-off points [14,17,34].…”
Section: Discussionmentioning
confidence: 99%